Preparation and Thermophysical Properties of Sodium Nitrate/Nanoparticle/Expanded Graphite Composite Heat Storage Material - Song, Wenbing; Lu, Yuanwei; Fan, Zhansheng; Wu, Yuting (Frontiers in Energy Research, 2022)
As a medium and high temperature heat storage medium, the thermal performance of molten salt plays an important role in the thermal energy storage system. In order to improve the specific heat capacity and thermal conductivity of molten salt, a mechanical dispersion method is used to prepare a shape-stable composite phase change material for thermal energy storage. Nitrate (NaNO3) has a higher phase change latent heat, which was chosen to combined with different nanoparticles (SiO2, SiO2+TiO2) to improve its specific heat capacity, and with expanded graphite (EG) as a carrier matrix to improve thermal conductivity. Through the characterization of its chemical compatibility and thermophysical properties, the results show that the nanoparticles, EG and NaNO3 have good chemical compatibility. Compared to NaNO3, the thermophysical properties of composite (NaNO3:(SiO2+TiO2):EG = 84%:0.1% + 0.9%:15%, mass ratio) was improved obviously. The average specific heat capacity before the phase change increased from 1.45 J/(g·K) to 1.81 J/(g·K), and the average specific heat capacity after the phase change increased from 1.69 J/(g·K) to 2.47 J/(g·K); The thermal conductivity is about 13.9 times higher than that of NaNO3; in the range of 100–380°C, the heat storage density of the composites is about 679.2 kJ/kg 300 thermal stability tests showed that the latent heat of the composites is reduced by 7.4%, and the specific heat capacity before and after the phase change is reduced by 6.1 and 6.0%, respectively. The research can provide a broad application prospects in the field of medium temperature energy storage.